Creating agroforestry innovation and best practice leaflets - Burgess, Paul J.; Moreno, Gerardo; Pantera, Anastasia; Kanzler, Michael; Hermansen, John E.; van Lerberghe, Philippe; Balaguer, Fabien; Girardin, Nicolas; Rosati, Adolfo; Graves, Anil; Watté, Jeroen; Mosquera-Losada, María Rosa; et al. (European Agroforestry Federation and the University of Santiago de Compostela, 2018)
A key output of the EU FP7 project AGFORWARD was a series of 46 agroforestry innovation and 10 agroforestry best practice leaflets for European farmers and other stakeholders. This paper describes the process of over 80 people working together to create the leaflets and the overall result.
Keywords: Promotion; Innovation; Dissemination; Communication; Internet